2023
DOI: 10.1183/23120541.00448-2022
|View full text |Cite
|
Sign up to set email alerts
|

Endobronchial ultrasound-guided transbronchial mediastinal cryobiopsy in the diagnosis of mediastinal lesions: safety, feasibility and diagnostic yield – experience in 50 cases

Abstract: BackgroundEndobronchial ultrasound guided transbronchial needle aspiration (EBUS-TBNA) is the technique of choice in the study of mediastinal and hilar lesions; however, it can be affected by the insufficiency of intact biopsy samples, which might decrease its diagnostic yield for certain conditions, thus requiring re-biopsies or additional diagnostic procedures such as mediastinoscopy when probability of malignancy remains high.ObjectivesOur objectives were to 1) attempt to reproduce this technique in the sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 33 publications
0
13
0
1
Order By: Relevance
“…This is mainly because of the need to obtain larger tissue samples for histological and molecular analysis. Several studies in the recent literature have already demonstrated the superiority of EBUS guided cryobiopsy over EBUS‐TBNA in terms of diagnostic yield for benign and lymphoproliferative diseases, with significantly low complication rate 2–5 . The most common adverse event is minor airway bleeding with no need for intervention, while the reported incidence of grade 3–4 bleeding is 2% 2,3 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is mainly because of the need to obtain larger tissue samples for histological and molecular analysis. Several studies in the recent literature have already demonstrated the superiority of EBUS guided cryobiopsy over EBUS‐TBNA in terms of diagnostic yield for benign and lymphoproliferative diseases, with significantly low complication rate 2–5 . The most common adverse event is minor airway bleeding with no need for intervention, while the reported incidence of grade 3–4 bleeding is 2% 2,3 .…”
Section: Discussionmentioning
confidence: 99%
“…Several studies in the recent literature have already demonstrated the superiority of EBUS guided cryobiopsy over EBUS‐TBNA in terms of diagnostic yield for benign and lymphoproliferative diseases, with significantly low complication rate. 2 , 3 , 4 , 5 The most common adverse event is minor airway bleeding with no need for intervention, while the reported incidence of grade 3–4 bleeding is 2%. 2 , 3 Therefore, in the case we presented, this technique appeared particularly indicated for several reasons such as: the central location of the consolidations, the visibility of the target on endobronchial ultrasound, the inconclusive ROSE, and the absence of vascular structures that could make the biopsy dangerous.…”
Section: Discussionmentioning
confidence: 99%
“…Ariza-Prota et al ( 11 ) conducted a prospective study in Spain on 50 patients, wherein participants underwent EBUS-TBNA followed by EBUS-TMC. Maturu et al ( 12 ) carried out a prospective study on 46 patients in India, in which EBUS-TMC was conducted if rapid on-site evaluation (ROSE) during EBUS-TBNA yielded insufficient or inconclusive results.…”
Section: Studiesmentioning
confidence: 99%
“…Endobronchial ultrasound-guided transbronchial lymph node cryobiopsy (EBUS-TBLCB) involves a similar technique as EBUS-IFB where a hole is first created in the airway for advancement of the cryoprobe. Multiple tools have been reported for this purpose, including needles with various gauges, electrocautery knife and Nd YAG Laser [60 ▪ ,61 ▪▪ ,62,63,64 ▪▪ ,65]. After freezing, the cryoprobe and EBUS scope are removed in block for specimen retrieval (Fig.…”
Section: Tissue Acquisition: How To Get Enough?mentioning
confidence: 99%
“…Procedure time is longer when cryobiopsy is added to TBNA but is well tolerated by patients even when receiving moderate sedation. Reported complications are rare and include bleeding, pneumothorax, and pneumomediastinum, infrequently requiring intervention outside of the bronchoscopy procedure [60 ▪ ,61 ▪▪ ,62]. Based on available data, EBUS-TBLCB may be superior to EBUS-TBNA in the diagnosis of rare thoracic malignancies and nonmalignant conditions, but the role in the diagnosis of typical lung cancers appears more complementary.…”
Section: Tissue Acquisition: How To Get Enough?mentioning
confidence: 99%